1
###
If the image of the point P(1, –2, 3) in the plane, 2x + 3y – 4z + 22 = 0

If the image of the point P(1, –2, 3) in the plane, 2x + 3y – 4z + 22 = 0 measured parallel to the line, x/1 = y/4 = z/5 is Q, then PQ is equal to:

- 3√5
- 2√42
- √42
- 6√5

2
###
The angle between the lines whose direction cosines satisfy

The angle between the lines whose direction cosines satisfy the equations l + m + n = 0 and l^{2} + m^{2} + n^{2} = 0 is

- π/2
- π/3
- π/4
- π/6

3
###
If the lines (x-1)/2 = (y+1)/2 = (z-1)/4 and (x-3)/1 = (y-k)/2 = z/1

If the lines (x - 1)/2 = (y + 1)/2 = (z - 1)/4 and (x - 3)/1 = (y - k)/2 = z/1 intersect, then k is equal to

- 9/2
- 2/9
- -1
- 0

4
###
If the angle between the line x = (y - 1)/2 = (z - 3)/λ and the plane

If the angle between the line x = (y - 1)/2 = (z - 3)/λ and the plane x + 2y + 3z = 4 is cos^{-1}(5/14) then λ is equal to

- 3/2
- 2/5
- 2/3
- 5/3

5
###
A line AB in three-dimensional space makes angles 45° and 120°

A line AB in three-dimensional space makes angles 45° and 120° with the positive x-axis and the positive y-axis respectively. If AB makes an acute angle θ with the positive z-axis, then θ equals

- 30°
- 45°
- 60°
- 75°

6
###
Let the line (x - 2)/3 = (y - 1)/-5 = (z - 2)/2 lie in the plane

Let the line (x - 2)/3 = (y - 1)/-5 = (z - 2)/2 lie in the plane x + 3y - αz + β = 0. Then (α, β) equals

- (-5, 5)
- (5, -15)
- (-6, 7)
- (6, -17)

7
###
The distance of the point (1,0,2) from the point of intersection

The distance of the point (1,0,2) from the point of intersection of the line (x - 2)/3 = (y + 1)/4 = (z - 2)/12 and the plane x - y + z = 16 is

- 13
- 8
- 3√21
- 2√14

8
###
A plane which passes through the point (3, 2, 0) and the line (x-4)/1 = (y-7)/5 = (z-4)/4 is

A plane which passes through the point (3, 2, 0) and the line (x-4)/1 = (y-7)/5 = (z-4)/4 is

- 2x - y + z = 5
- x + 2y - z = 1
- x - y + z = 1
- x + y + z = 5

9
###
If the line lies in the plane, lx + my – z = 9, then l^2 + m^2 is equal to

If the line, (x-3)/2 = (y+2)/-1 = (z+4)/3, lies in the plane, lx + my – z = 9, then l^{2} + m^{2} is equal to:

- 18
- 5
- 2
- 26